Insights Into the Mechanisms of Brain Endothelial Erythrophagocytosis - Sun, Jiahong; Vyas, Prema; Mann, Samar; Paganini-Hill, Annlia; Nunes, Ane C. F.; Lau, Wei Ling; Cribbs, David H.; Fisher, Mark J.; Sumbria, Rachita K. (Frontiers in Cell and Developmental Biology, 2021)
The endothelial cells which form the inner cellular lining of the vasculature can act as non-professional phagocytes to ingest and remove emboli and aged/injured red blood cells (RBC) from circulation. We previously demonstrated an erythrophagocytic phenotype of the brain endothelium for oxidatively-stressed RBC with subsequent migration of iron-rich RBC and RBC degradation products across the brain endothelium in vivo and in vitro, in the absence of brain endothelium disruption. However, the mechanisms contributing to brain endothelial erythrophagocytosis are not well defined, and herein we elucidate the cellular mechanisms underlying brain endothelial erythrophagocytosis. Murine brain microvascular endothelial cells (bEnd.3 cells) were incubated with tert-butyl hydroperoxide (tBHP; oxidative stressor to induce RBC aging in vitro)- or PBS (control)-treated mouse RBC. tBHP increased reactive oxygen species (ROS) formation and phosphatidylserine exposure in RBC, which were associated with robust brain endothelial erythrophagocytosis. TNFα treatment potentiated brain endothelial erythrophagocytosis of tBHP-RBC in vitro. Brain endothelial erythrophagocytosis was significantly reduced by RBC phosphatidylserine cloaking with annexin-V and with RBC-ROS and phosphatidylserine reduction with vitamin C. Brain endothelial erythrophagocytosis did not alter bEnd.3 viability, and tBHP-RBC were localized with early and late endosomes. Brain endothelial erythrophagocytosis increased bEnd.3 total iron pool, abluminal iron levels without causing brain endothelial monolayer disruption, and ferroportin levels. In vivo, intravenous tBHP-RBC injection in aged (17-18 months old) male C57BL/6 mice significantly increased Prussian blue-positive iron-rich lesion load compared with PBS-RBC-injected mice. In conclusion, RBC phosphatidylserine exposure and ROS are key mediators of brain endothelial erythrophagocytosis, a process which is associated with increased abluminal iron in vitro. tBHP-RBC result in Prussian blue-positive iron-rich lesions in vivo. Brain endothelial erythrophagocytosis may provide a new route for RBC/RBC degradation product entry into the brain to produce iron-rich cerebral microhemorrhage-like lesions.